The anaerobic power reserve and its applicability in professional road cycling - Sanders, D.; Heijboer, M. (Journal of Sports Sciences, 2019)
This study examined if short-duration record power outputs can be predicted with the Anaerobic Power Reserve (APR) model in professional cyclists using a field-based approach. Additionally, we evaluated if modified model parameters could improve predictive ability of the model. Twelve professional cyclists (V?O2max 75 ± 6 ml·kg-1·min-1) participated in this investigation. Using the mean power output during the last stage of an incremental field test, sprint peak power output and an exponential constant describing the decrement in power output over time, a power-duration relationship was established for each participant. Record power outputs of different durations (5 to 180 s) were collected from training and competition data and compared to the predicted power output from the APR model. The originally proposed exponent (k = 0.026) predicted performance within an average of 43 W (Standard Error of Estimate (SEE) of 32 W) and 5.9%. Modified model parameters slightly improved predictive ability to a mean of 34-39 W (SEE of 29 - 35 W) and 4.1 - 5.3%. This study shows that a single exponent model generally fits well with the decrement in power output over time in professional cyclists. Modified model parameters may contribute to improving predictability of the model.